2009
DOI: 10.1111/j.1600-6143.2008.02462.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Correlates of Scarring in Kidney Transplants: The Emergence of Mast Cell Transcripts

Abstract: In the Banff consensus, infiltrates in areas of scarring are ignored. This study aimed to characterize the molecular correlates and clinical significance of scarring and inflammation in scarred areas.We assessed the extent of interstitial infiltrates, tubulitis and scarring in 129 clinically indicated renal allograft biopsies, and correlated the results with microarray expression data and allograft survival. Findings were validated in 50 additional biopsies.Transplants with scarring had a worse prognosis if th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
79
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(91 citation statements)
references
References 35 publications
6
79
0
4
Order By: Relevance
“…(5). The molecular phenotype is reviewed in a companion paper (6) but the lessons from the molecular studies are incorporated here to propose an integrated approach to interpreting biopsy findings and outcomes, (13), mast cell transcripts (14) and FOXP3 mRNA (15). (22).…”
Section: Much Has Changed Since 2002 the Term Chronic Allograft Nephmentioning
confidence: 99%
“…(5). The molecular phenotype is reviewed in a companion paper (6) but the lessons from the molecular studies are incorporated here to propose an integrated approach to interpreting biopsy findings and outcomes, (13), mast cell transcripts (14) and FOXP3 mRNA (15). (22).…”
Section: Much Has Changed Since 2002 the Term Chronic Allograft Nephmentioning
confidence: 99%
“…We previously reported that fibrosis in human kidney transplants was associated with transcripts expressed in certain inflammatory cells: mast cell transcripts (MCATs) such as carboxypeptidase 3 (CPA3) (26) and immunoglobulin transcripts (IGTs) representing plasma cells (27). Such transcripts do not correlate with TCMR or ABMR.…”
Section: Funding Canada Foundation For Innovation and Genome Canadamentioning
confidence: 99%
“…27; MCATs, ref. 26; and AKI and FICOL transcripts, ref. 14); then we explored all fibrosis-associated transcript changes, correcting for the time of the biopsy after transplant (TxBx).…”
Section: Funding Canada Foundation For Innovation and Genome Canadamentioning
confidence: 99%
“…As might be expected, the noncompliant patients demonstrated more inflammatory changes but were also found to have more interstitial fibrosis and identical degrees of arteriolar hyalinosis than the compliant patients. In kidney transplantation, it is now becoming apparent that the presence of fibrosis and atrophy may not predispose to graft failure; a more critical variable is evidence of ongoing inflammation (47,48). In a recent report from the Deterioration of Kidney Allograft Function study group (49), 60% of patients with allograft dysfunction 7 yr after transplantation had donor-specific antibody, C4d staining, or both.…”
Section: Alternatives To An Incomplete Paradigmmentioning
confidence: 99%